2000
DOI: 10.1021/jm000939v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Ceramide Analogues with Substituted Aromatic Rings or an Allylic Fluoride in the Sphingoid Moiety

Abstract: The biological activity of synthetic ceramide analogues, having modified sphingoid and N-acyl chains, as well as fluorine substituents in the allylic position, was investigated in hippocampal neurons. Their influence on axonal growth was compared to that of C(6)-N-acyl analogues of natural ceramides. D-erythro-Ceramides with a phenyl group in the sphingoid moiety and a short N-acyl chain were able to reverse the inhibitory effect of fumonisin B(1) (FB(1)), but not of D-threo-1-phenyl-2-decanoylamino-3-morpholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Specifically, we have used novel ceramide analogs that are altered with respect to the degree and position of unsaturation of bonds in the sphingoid backbone of D-erythro-N-octanoyl-ceramide. Others have demonstrated that changes in ceramide's structure can result in increased efficacy of these compounds (Wieder et al, 1997;Van Overmeire et al, 2000;Macchia et al, 2001;Chun et al, 2003b). For example, Macchia et al (2001) used DNA fragmentation and release of cytochrome c to analyze the effect of replacing the polar portion of the ceramide molecule with uracil or thiouracil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we have used novel ceramide analogs that are altered with respect to the degree and position of unsaturation of bonds in the sphingoid backbone of D-erythro-N-octanoyl-ceramide. Others have demonstrated that changes in ceramide's structure can result in increased efficacy of these compounds (Wieder et al, 1997;Van Overmeire et al, 2000;Macchia et al, 2001;Chun et al, 2003b). For example, Macchia et al (2001) used DNA fragmentation and release of cytochrome c to analyze the effect of replacing the polar portion of the ceramide molecule with uracil or thiouracil.…”
Section: Discussionmentioning
confidence: 99%
“…This selectivity of location of unsaturation in the sphingoid backbone is supported by our data, because 6-ene-Cer, which has the unsaturation only at C(6)-C(7), was considerable less potent than analogs that contained a C(4)-C(5) trans double bond (with the exception of 4,6-diene-7-Ph-Cer), with an IC 50 value of 43.2 M. However, the presence of the C(4)-C(5) and C(6)-(C)7 double bonds alone is not sufficient to confer increased efficacy as 4,6-diene-7-Ph-Cer did not induce greater than 55% cell death at concentrations up to 100 M. The replacement of the long-chain base with a phenyl group may alter the lipophilicity of the compound such that it is not taken up efficiently or inserted into cellular membranes. Van Overmeire et al (2000) also investigated ceramide analogs with an aromatic ring similar to 4,6-diene-7-Ph-Cer and found these compounds to be very effective. However, it is difficult to correlate these results with those in the present study because the biological response measured in that study dealt with overcoming axonal growth inhibition in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The compounds 1,3,6-tribromopyrene [35] (17), 2-ethynylthiophene, [36] octa(ethylene glycol) monomethyl ether, [37] 1,6-diiodopyrene…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, ceramides with a phenyl group in the sphingoid moiety and a short N-acyl chain (81−85) were able to reverse that inhibitory effect [116]. Those aromatic analogs were recognized as a substrate by glucosylceramide synthase, which suggests that the observed biological effects were mediated by activation of the ceramide analog via glucosylation.…”
Section: Sphingolipids In Anticancer Therapymentioning
confidence: 99%
“…The aminopentol backbone AP 1 (116) by itself was a weak inhibitor of CS. In the presence of palmitoyl-CoA AP 1 (116) was acylated to form N-palmitoyl-AP 1 (PAP 1 , 117):…”
Section: Cs Inhibitorsmentioning
confidence: 99%